Gender Parity Key to Sustainable Development in Africa: A Reading of Margaret Ogola’s Characterization in The River and the Source and I Swear by Apollo - Jose , Anne Jerono (African Journal of Education,Science and Technology (AJEST), 2014)
This paper is a reading of Margaret Ogola‟s projection of the contributions womenfolk have made towards the social, political and economic development in African society from pre-colonial times right through the post colonial period in the two novels The River and the Source and I swear by Apollo. Focusing on social structure as instrumental in the politics of exclusion that African women have had to endure for so long, the paper seeks to examine the author‟s exploration of social intercourse as depicted in the two texts. Women constitute more than half of the world‟s population. Their contribution to social and economic development is monumental yet in many of African cultures they have been ignored as equal partners. Gender-based inequality is demonstrated in African culture as sources of suppression of the development potential in women. However, the thrust of the texts‟ argument is that enabling the population regardless of gender to actively participate in social and economic well-being is crucial for long term and sustainable social, political and economic development of any society. It is against this backdrop that the proposed paper seeks to locate Margaret Ogola‟s novels within the thematic frame of gender inequality in Kenyan society. The paper also intends to bring out the causes and possibilities open to the problem of gender disparity as envisaged by the author in the two texts.